An Analysis of Lard by using Dielectric Sensing Method - Khamil, K.N.; Yin, C.K. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2016)
Culinary often uses lard to enhance the flavour and crispiness of food. But foods containing lard or fat from pig is non-permissible for Muslim and vegetarian. Due to that, lard detection technique is becoming an important element in the food industry. This research conducted a potential rapid first stage screening of lard using a dielectric sensing method of interdigitated electrode (IDE) to measure the impedance value of lard. The measurement is taken using LCR meter EDC-1630, which is capable to supply frequency in between the range of 100Hz to 100 kHz. The IDE is optimised using TAGUCHI method where the best optimisation result consists of 42 number of an electrode. The graph of the result shows the relationship of impedance, frequency supplied and a number of reheating hour. Data were analysed using statistical method linear regression to prove the relationship of impedance and number of reheating hours. The results show that R-square value for IDE 42 was more constant compare to other IDE, which was at 0.96 to 0.98.